Differential symptomology of possible and confirmed Ebola virus disease infection in the Democratic Republic of the Congo: a retrospective cohort study. Issue 1 (January 2023) - Nsio, Justus; Ardiet, Denis-Luc; Coulborn, Rebecca M; Grellety, Emmanuel; Albela, Manuel; Grandesso, Francesco; Kitenge, Richard; Ngwanga, Dolla L; Matady, Bibiche; Manangama, Guyguy; Mossoko, Mathias; Ngwama, John Kombe; et al.
Summary: Background: In its earliest phases, Ebola virus disease's rapid-onset, high fever, and gastrointestinal symptoms are largely indistinguishable from other infectious illnesses. We aimed to characterise the clinical indicators associated with Ebola virus disease to improve outbreak response. Methods: In this retrospective analysis, we assessed routinely collected data from individuals with possible Ebola virus disease attending 30 Ebola health facilities in two provinces of the Democratic Republic of the Congo between Aug 1, 2018, and Aug 28, 2019. We used logistic regression analysis to model the probability of Ebola infection across 34 clinical variables and four types of possible Ebola virus disease exposures: contact with an individual known to have Ebola virus disease, attendance at any funeral, health facility consultation, or consultation with an informal health practitioner. Findings: Data for 24 666 individuals were included. If a patient presented to care in the early symptomatic phase (ie, days 0–2), Ebola virus disease positivity was most associated with previous exposure to an individual with Ebola virus disease (odds ratio [OR] 11·9, 95% CI 9·1–15·8), funeral attendance (2·1, 1·6–2·7), or health facility consultations (2·1, 1·6–2·8), rather than clinical parameters. If presentation occurred on day 3 or later (after symptom onset), bleeding at an injection site (OR 33·9, 95% CI 12·7–101·3), bleeding gums (7·5, 3·7–15·4), conjunctivitis (2·4, 1·7–3·4), asthenia (1·9, 1·5–2·3), sore throat (1·8, 1·3–2·4), dysphagia (1·8, 1·4–2·3), and diarrhoea (1·6, 1·3–1·9) were additional strong predictors of Ebola virus disease. Some Ebola virus disease-specific signs were less prevalent among vaccinated individuals who were positive for Ebola virus disease when compared with the unvaccinated, such as dysphagia (–47%, p=0·0024), haematemesis (–90%, p=0·0131), and bleeding gums (–100%, p=0·0035). Interpretation: Establishing the exact time an individual first had symptoms is essential to assessing their infection risk. An individual's exposure history remains of paramount importance, especially in the early phase. Ebola virus disease vaccination reduces symptom severity and should also be considered when assessing the likelihood of infection. These findings about symptomatology should be translated into practice during triage and should inform testing and quarantine procedures. Funding: Médecins Sans Frontières and its research affiliate Epicentre.